FAKTOR-FAKTOR YANG MEMENGARUHI AUDIT DELAY DI PERUSAHAAN MANUFAKTUR (Media Riset Akuntansi, 2022)
This study aims to analyze how big the effect of firm size, auditor characteristics, audit opinion, audit tenure, auditor turnover and earnings management to audit delay at manufacturing companies listed on Indonesia Stock Exchange period 2013-2016. The sample selection using purposive sampling method. Data analysis method used is quantitative approach by using multiple linear regression. Based on the research that has been done on the manufacturing sector companies listed on the Indonesia Stock Exchange, it can be concluded that firm size, auditor characteristics and audit tenure effect on audit delay. The size of the company and the ignorance of the auditor in understanding the client industry and the length of the auditor in auditing the financial statements, this resulted in the occurrence of audit delay. Meanwhile, audit opinion, auditor turnover and earnings management have no effect on audit delay.